Legal Aspects of Using Special Methods for Stammping Out Organized Crime in Serbia and Montenegro - Milošević, Milan (Kriminalističke teme, 2003)
Protective function of the criminal legislation prescibes usage of adequate methods and mesoures. It is especially worth for transnational organized crime, wictimless crime, serious crime with, the tendency of profesionalization, etc. However, the usage of traditional and special (conspirative) means and methods in criminal proceeding is directly influences by the two opposing tendencies of the criminal proceeding low: the need for complete protection of the right and freedoms of a citizen, and, on the other hand, the need for optimal eficiency of criminal proceeding. Therefore, every legislative measure which assumes norming of special methods for stamping out organized crime, has to be well thought-out and suitable. The legislation of Serbia and Montenegro has recently standardized special methods (measures and actions) in the Law of Criminal Procedure. Therefore, there must not be any dilema about the value of the evidences that are methods. On the other hand, some etical and legal dilemas may be present about the usage of results of there methods, especially undercover policing - infiltration by police in the criminal miliey and police provocation to criminal deed. Proceeding from this assumption, this article presents the usage of special means and methods for stamping out organized crime.